Synthesis and Nonlinear Optical Properties of Au and ZnO Nanoparticles and Their Nanocomposites (Journal of the College of Basic Education, 2026)
This Study elaborates on the synthesis and nonlinear optical characteristics of gold (Au) and zinc oxide (ZnO) nanoparticles and nanocomposites (ZnO-Au NCs), which are prepared by pulsed laser ablation in liquid (PLAL) approach. ZnO is a year-wide bandgap semiconductor with high exciton binding energy (60 meV) that is economical, environmentally friendly, and non-toxic thus it is suitable in optical and electronic devices. Characterizations of the synthesized nanoparticles were done by X-ray diffraction (XRD), energy dispersive X-ray (EDX), ultraviolet-visible (UV-Vis) spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, field emission scanning electron microscopy (FESEM), and transmission electron microscopy (TEM). The results show that, ZnO- Au nanocomposites have better nonlinear optical properties than the original Au and ZnO nanoparticles. The nonlinear refractive index (n2) of ZnO-Au NCs was determined to be 3.27 x 104 cm2 /GW, which is much higher than that of pure ZnO (3.7 x 104 cm2 /GW ). Another technique used in the study to obtain the nonlinear optical parameters was the Z-scan in which, it was found that the inclusion of Au in ZnO increases light absorption by the surface plasmon resonance (SPR) effect. The study exudes the potential of ZnO-Au nanocomposites in the future of the design of advanced nonlinear photonic devices and environmental remediation, which is a clean and efficient way of synthesizing functional nanomaterials.